2004
DOI: 10.1128/jcm.42.1.276-285.2004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Multilocus Sequence Typing and Pulsed-Field Gel Electrophoresis for Characterizing Listeria monocytogenes Strains Isolated from Environmental and Clinical Sources

Abstract: One hundred seventy-five Listeria monocytogenes strains were characterized by serotyping, pulsed-field gel electrophoresis (PFGE), and multilocus sequence typing (MLST) based on loci in actA, betL, hlyA, gyrB, pgm, and recA. One hundred twenty-two sequence types (STs) were identified by MLST based on allelic profiles of the four housekeeping genes (betL, gyrB, pgm, and recA), and 34 and 38 alleles were identified for hlyA and actA, respectively. Several actA and hlyA alleles appeared to be predominantly associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
2
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 33 publications
6
68
2
4
Order By: Relevance
“…MLST is just as applicable to global epidemiology as MLEE, while providing better discriminatory power and ensuring inter-laboratory data-sharing (Chan et al, 2001). Unfortunately, it is time-consuming and expensive, and a common MLST test suitable for L. monocytogenes does not exist for epidemiological studies (Revazishvili et al, 2004;Nightingale et al, 2010).…”
Section: Ecology Of Listeria Monocytogenes and Molecular Subtyping Mementioning
confidence: 99%
“…MLST is just as applicable to global epidemiology as MLEE, while providing better discriminatory power and ensuring inter-laboratory data-sharing (Chan et al, 2001). Unfortunately, it is time-consuming and expensive, and a common MLST test suitable for L. monocytogenes does not exist for epidemiological studies (Revazishvili et al, 2004;Nightingale et al, 2010).…”
Section: Ecology Of Listeria Monocytogenes and Molecular Subtyping Mementioning
confidence: 99%
“…Currently, alternative molecular typing methods such as multilocus sequence typing (MLST) and virulotyping [1,[14][15] are used to characterize many Salmonella enterica serovars. Multilocus sequence typing [16] has been increasingly recognized as a method of choice for genotyping a number of bacterial pathogens [17][18], including Salmonella [1,[19][20][21], and has been used successfully in epidemiological studies and outbreak investigations [17,22]. This technique is based on determination of the DNA sequence of a series of selected housekeeping, ribosomal, and/or virulenceassociated genes [23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have investigated MLST of L. monocytogenes and shown that the method is a powerful typing-tool for epidemiology (Revazishvili et al, 2004;Salcedo et al, 2003;Zhang et al, 2004). In particular, MLST using virulence genes seems to be more discriminatory than the standard protocol for epidemiology, PFGE (Revazishvili et al, 2004;Zhang et al, 2004). Thus, like MLST, the SNP typing method based on comparison of the virulence genes of L. monocytogenes could become an effective tool for subtyping isolates of L. monocytogenes.…”
Section: Discussionmentioning
confidence: 99%
“…Many isolates from food or environment were categorized into the same SNP types (characteristic examples; A5, B12-B14, C14) or MLST types (MLST-2, -4, -10, and -12) as clinical isolates, suggesting that these isolates from food or environment may be capable of causing food poisoning. Several researchers have investigated MLST of L. monocytogenes and shown that the method is a powerful typing-tool for epidemiology (Revazishvili et al, 2004;Salcedo et al, 2003;Zhang et al, 2004). In particular, MLST using virulence genes seems to be more discriminatory than the standard protocol for epidemiology, PFGE (Revazishvili et al, 2004;Zhang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%